Recent Advances in Corpus Linguistics Developing and Exploiting Corpora. - Vandelanotte, Lieven (Editions Rodopi, 2014)
This book is a selection of studies presented at the 33rd International Conference of the International Computer Archive of Modern and Medieval English (ICAME), hosted by the University of Leuven (30 May - 3 June 2012). The strictly refereed and extensively revised contributions collected here represent recent advances in corpus linguistics, both in the development of specialist corpora and in ways of exploiting them for specific purposes. The first part focuses on "Corpus development and corpus interrogation" and features papers on the compilation of new, highly specialized corpora which aim.